Sistem Penilaian Kebutuhan Dan Monitoring Bantuan Penderita Kusta Di Kabupaten Gresik - Wahyudi, Hendra; Wurijanto, Tutut; Lusiani, Titik (Jurnal JSIKA, 2012)
A needs assessment is an activity to identify a need of someone who needed attention more than others due to lack of physical, social or economic. And monitoring development assistance is to monitor the activities of an object that has channeled aid to the recipient bantuan.Becouse yet there is a facility or information system tools that can assist in the assessment and monitoring needs assistance. Monitoring is needed as a benchmark indicator to monitor the development assistance. Monitoring is to help see the development of leprosy patients.   Keywords: Leprosy, Monitoring, Stigma of Leprosy